2011
DOI: 10.1029/2011gl048980
|View full text |Cite
|
Sign up to set email alerts
|

Using the NARMAX approach to model the evolution of energetic electrons fluxes at geostationary orbit

Abstract: Recently published data from Reeves et al. (2011) on the fluxes of 1.8–3.5 MeV electrons at geostationary orbit are subjected to Error Reduction Ratio (ERR) analysis in order to identify the parameters that control variance of these fluxes. ERR shows that it is the solar wind density not the velocity that controls most of the variance of the energetic electrons fluxes. High fluxes are observed under the conditions of low density in absolute majority of cases. Under the condition of fixed density the dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
173
3
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(189 citation statements)
references
References 22 publications
(47 reference statements)
10
173
3
3
Order By: Relevance
“…A very different approach is used in the SNB3GEO models (Balikhin et al 2011;Boynton et al 2015Boynton et al , 2016) based on Multi-Input Single-Output (MISO) Nonlinear AutoRegressive Moving Average with eXogenous inputs (NARMAX) methodologies (Leontaritis and Billings 1985a,b). In the applied system identification approach, models are automatically deduced from input-output data by the system identification algorithms.…”
Section: Ring Current Electrons and Effects On Satellitesmentioning
confidence: 99%
“…A very different approach is used in the SNB3GEO models (Balikhin et al 2011;Boynton et al 2015Boynton et al , 2016) based on Multi-Input Single-Output (MISO) Nonlinear AutoRegressive Moving Average with eXogenous inputs (NARMAX) methodologies (Leontaritis and Billings 1985a,b). In the applied system identification approach, models are automatically deduced from input-output data by the system identification algorithms.…”
Section: Ring Current Electrons and Effects On Satellitesmentioning
confidence: 99%
“…Within the radiation belts, magnetosonic waves form an integral part of the mechanism to accelerate electrons to very high energies (Friedel et al, 2002;Horne et al, 2007). However, it is still unclear which external influence modulate the generation mechanism of these electrons (Reeves et al, 2011;Balikhin et al, 2011;Boynton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has recently been applied to various energies of the electron flux ranging from 24.1 keV to 3.5 MeV, obtaining some unexpected results (Boynton et al, 2013;Balikhin et al, 2011). Balikhin et al (2011) found that for 1.8-3.5 MeV electrons, the solar wind density had the most influence. The following study by Boynton et al (2013) reported an increasing influence in density from ∼ 1 until 1.8 MeV, above which it became the most important control parameter for the electron fluxes at GEO.…”
Section: Introductionmentioning
confidence: 99%
“…This study produced a new coupling function that was then used as an input to model the Dst index in a following paper (Boynton et al, 2011a). This technique has recently been applied to various energies of the electron flux ranging from 24.1 keV to 3.5 MeV, obtaining some unexpected results (Boynton et al, 2013;Balikhin et al, 2011). Balikhin et al (2011) found that for 1.8-3.5 MeV electrons, the solar wind density had the most influence.…”
Section: Introductionmentioning
confidence: 99%